2017
DOI: 10.1080/1547691x.2016.1254306
|View full text |Cite
|
Sign up to set email alerts
|

Association between perfluoroalkyl substance exposure and asthma and allergic disease in children as modified by MMR vaccination

Abstract: Perfluoroalkyl substances (PFAS) are highly persistent chemicals that might be associated with asthma and allergy, but the associations remain unclear. Therefore, this study examined whether pre- and post-natal PFAS exposure was associated with childhood asthma and allergy. Measles, mumps and rubella (MMR) vaccination in early life may have a protective effect against asthma and allergy and is therefore taken into account when evaluating these associations. In a cohort of Faroese children whose mothers were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 42 publications
(63 reference statements)
4
38
0
Order By: Relevance
“…In regard to T H 2-related allergy, increased odds of asthma in children were reported at elevated PFAS exposures (Dong et al 2013), although this finding has not been replicated (Humblet et al 2014). Our own studies (i.e., Timmermann et al 2017) suggested that serum-PFAS concentrations at age 5 years were associated with increased odds of asthma only among the children who had not yet been vaccinated against measles, mumps, and rubella (MMR), while the association was reversed among MMR-vaccinated children. Although inhibition of antibody responses, perhaps associated with increased risk of allergy development, could represent a change in the T H 1/T H 2 balance (Dong et al 2011), the relative role of the immune system components is complex.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…In regard to T H 2-related allergy, increased odds of asthma in children were reported at elevated PFAS exposures (Dong et al 2013), although this finding has not been replicated (Humblet et al 2014). Our own studies (i.e., Timmermann et al 2017) suggested that serum-PFAS concentrations at age 5 years were associated with increased odds of asthma only among the children who had not yet been vaccinated against measles, mumps, and rubella (MMR), while the association was reversed among MMR-vaccinated children. Although inhibition of antibody responses, perhaps associated with increased risk of allergy development, could represent a change in the T H 1/T H 2 balance (Dong et al 2011), the relative role of the immune system components is complex.…”
Section: Discussionmentioning
confidence: 96%
“…The Faroese Cohort 5 of 490 children was recruited from births at the National Hospital in Tórshavn, Faroe Islands, during 2007–2009 (Kim et al 2014; Timmermann et al 2017). A maternal serum sample was collected about two weeks after the expected term date.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only one prospective study investigated both prenatal and childhood exposures to PFASs and hypersensitivity outcomes, and reported increased odds of asthma at ages 5 and 13 with higher levels of PFASs at age 5, but only among children not vaccinated for measles, mumps and rubella. The same study found no associations between maternal prenatal PFASs concentrations and IgE levels, childhood asthma or allergic diseases [57] at ages 5 and 13.…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
“…Thirteen studies reported on autoimmunity/hypersensitivity endpoints in eight prospective birth cohorts from Canada [45], Japan [61, 62, 63], Taiwan [65], Faroe Islands [57], Greenland, Ukraine [60], Norway [58] and from four cross-sectional studies in Taiwan [66] and the USA (NHANES) [4648]. Higher IgE levels in 2-year-old Taiwanese children were observed with higher cord blood PFOS and PFOA concentrations, but no associations were found for atopic dermatitis at the same age [65].…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%